2011
DOI: 10.1029/2010jf001878
|View full text |Cite
|
Sign up to set email alerts
|

A model for fire-induced sediment yield by dry ravel in steep landscapes

Abstract: [1] Sediment flux from hillslopes to channels commonly increases following wildfires, with implications for the carbon cycle, river habitats, and debris-flow hazards. Although much of this material is transported via dry ravel, existing ravel models are not applicable to hillslopes with gradients greater than the angle of repose, which can constitute the majority of mountainous terrain. To fill this knowledge gap, we develop a continuity model for sediment storage by vegetation dams on steep hillslopes to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
159
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(167 citation statements)
references
References 32 publications
4
159
0
Order By: Relevance
“…In the model, the volume of sediment stored on hillslopes is a function of chaparral vegetation density, capacity of plants to impound sediment, and the contributing hillslope area. As noted by Lamb et al (2011), in models developed by Roering and Gerber (2005) and Gabet (2003), the dry-ravel flux predicted is infinite when slope is greater than the angle of repose, such that on steep slopes without vegetation, flux is limited by supply. Therefore, it is critical to consider the time needed to establish vegetation between fires, the time needed for bedrock to weather and replenish hillslope stored sediment, and the fire recurrence interval.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the model, the volume of sediment stored on hillslopes is a function of chaparral vegetation density, capacity of plants to impound sediment, and the contributing hillslope area. As noted by Lamb et al (2011), in models developed by Roering and Gerber (2005) and Gabet (2003), the dry-ravel flux predicted is infinite when slope is greater than the angle of repose, such that on steep slopes without vegetation, flux is limited by supply. Therefore, it is critical to consider the time needed to establish vegetation between fires, the time needed for bedrock to weather and replenish hillslope stored sediment, and the fire recurrence interval.…”
Section: Introductionmentioning
confidence: 99%
“…Dry ravel is a dominant sediment transport process in steep chaparral regions (Krammes, 1965;Rice, 1974;1982) where slope is greater than the angle of repose (Lamb et al, 2011). Early research showed high sediment flux rates on steep chaparral slopes (Anderson, et al, 1959;Krammes, 1965).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment flux generally rises after wildfire due to increases in the erodibility of hillslope surfaces through the removal of vegetation and litter layers, destabilization of soil aggregates by organic matter combustion, and increases in soil mantle slides or overland flow due to the development of subsurface and surface soil hydrophobicity, respectively (Debano and Krammes, 1966;Keller et al, 1997;DeBano, 2000;Gabet, 2003). In systems experiencing dry seasons, such as much of the Western U.S., this results in down-slope 5 dry-ravel transport through gravity alone (Swanson, 1981;Jackson and Roering, 2009;Lamb et al, 2011;Hubbert et al, 2012). Soil heating can also cause hydrophobicity increases in the soil surface that, along with decreases in interception and evapotranspiration, cause increases in surface runoff during the wet season (Shakesby and Doerr, 2006).…”
Section: Internal and External Controlsmentioning
confidence: 99%